1988
DOI: 10.1007/bf01342644
|View full text |Cite
|
Sign up to set email alerts
|

Sensory interaction with central ?generators? during respiration in the dogfish

Abstract: The activity in sensory and motor nerves of the gills was recorded from selected branches of the vagus nerve in decerebrate dogfish, Scyliorhinus canicula. Vagal motoneuronal activity was observed at the start of the rapid pharyngeal contraction and was followed by sensory nerve activity which preceded the slow expansion phase. Rhythmical vagal motoneuronal activity was still present after all movements had been prevented by curare paralysis although the frequency of the rhythm was higher than in the ventilati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1992
1992
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…Effect of a model predator on mean (‫ע‬SE) time lag to the onset of aquatic surface respiration (ASR; a), number of ASR episodes (b), and total time spent at the surface performing ASR (c) following an external application of 2 mg NaCN into the ventilatory stream via a buccal cannula in Mugil cephalus in turbid water containing 300 NTU Polsperse 10 kaolin at a temperature of 25ЊC and salinity of 36‰. activity in teleost fish are known to reside in the medulla (Hughes and Shelton 1962;Ballintijn 1988;Sundin et al 2003), and this also appears to be the case for air-breathing reflexes in bimodal fish (Wilson et al 2000), but very little is known about how reflex activity is modified by inputs from higher centers (Ballintijn and Juch 1984;Roberts and Ballintijn 1988;Taylor et al 1999). Tracing of the sensory afferents from the gills and of the motor efferents serving the gills and heart found that these did not make contact in the medulla of the shorthorn sculpin Myoxocephalus scorpius (Sundin et al 2003).…”
Section: Modulatory Effect Of the Model Predator On O 2 Chemoreflexesmentioning
confidence: 99%
“…Effect of a model predator on mean (‫ע‬SE) time lag to the onset of aquatic surface respiration (ASR; a), number of ASR episodes (b), and total time spent at the surface performing ASR (c) following an external application of 2 mg NaCN into the ventilatory stream via a buccal cannula in Mugil cephalus in turbid water containing 300 NTU Polsperse 10 kaolin at a temperature of 25ЊC and salinity of 36‰. activity in teleost fish are known to reside in the medulla (Hughes and Shelton 1962;Ballintijn 1988;Sundin et al 2003), and this also appears to be the case for air-breathing reflexes in bimodal fish (Wilson et al 2000), but very little is known about how reflex activity is modified by inputs from higher centers (Ballintijn and Juch 1984;Roberts and Ballintijn 1988;Taylor et al 1999). Tracing of the sensory afferents from the gills and of the motor efferents serving the gills and heart found that these did not make contact in the medulla of the shorthorn sculpin Myoxocephalus scorpius (Sundin et al 2003).…”
Section: Modulatory Effect Of the Model Predator On O 2 Chemoreflexesmentioning
confidence: 99%
“…produce a complete cessation of breathing, even in conscious animals (21,51,87,88,91,97,98,114). In all cases, addition of a tonic respiratory drive (such as elevated PCO 2 or descending input from higher centers, such as the pons) restores a phasic (rhythmic) respiratory output.…”
Section: Expression Of a Respiratory Rhythm Is Conditional On (Tonic)mentioning
confidence: 99%
“…These empirical studies and theoretical considerations have led to the conclusion that in everything from unanesthetized animals to the most reduced preparations, respiratory rhythm is critically dependent on respiratory drive. They also suggest that respiratory neurons in the brain stem operate at a subthreshold level that requires some external stimulus to bring the system to threshold, allowing the expression of respiratory events (21,24,51,87,88,91,97,98,114) (Fig. 2).…”
Section: Expression Of a Respiratory Rhythm Is Conditional On (Tonic)mentioning
confidence: 99%
“…Respiratory rhythm in the dogfish is known to be centrally generated (Ballintijn et al 1983). Efferent respiratory units are found in cranial nerves V, VII, IX and X, and it is known that electrical stimulation of these respiratory nerves effects respiratory output (Roberts & Ballintijn, 1988 In all animals central, electrical stimulation above a threshold value of 200-400 mV (average 270 mV), resulted in a distinct alteration of efferent respiratory activity. In 14 of 16 fish entrainment of the respiratory bursts was achieved, though the range over which entrainment occurred (capture range) varied markedly.…”
Section: Referencesmentioning
confidence: 99%